Could the conservative approach be considered safe in the treatment of locally advanced rectal cancer in case of a clinical near-complete or complete response? A retrospective analysis. (May 2021) - Chiloiro, Giuditta; Meldolesi, Elisa; Giraffa, Martina; Capocchiano, Nikola Dino; Barbaro, Brunella; Coco, Claudio; Corvari, Barbara; De Franco, Paola; D'Ugo, Domenico; Alfieri, Sergio; Manfredi, Riccardo; Valentini, Vincenzo; et al.
Abstract: Background: Conservative approach has emerged as an option for the management of rectal cancer (RC) patients with a near or complete clinical response after neoadjuvant chemoradiotherapy (nCRT). The aim of this study is to assess the impact of the conservative approach by comparing patients' survival outcomes and quality of life with those who had surgical resection. Methods: A single-institution and retrospective study including RC patients who reached a near complete or complete clinical response after nCRT from January 2010 to September 2019. Conservative approaches included local excision or watch and wait strategy; surgery approaches included anterior resection or abdominal-perineal resection. Local regrowth (LR), overall survival, disease free survival, metastasis free survival and colostomy free survival were evaluated through Kaplan-Meier curves and compared trough log-rank tests. Quality of life was measured by the following validated questionnaires: EORTC QLC30, EORTC QLQ – CR29 and Fecal Incontinence Quality of Life scale. Results: Overall 157 patients were analyzed: 105 (66, 9%) underwent radical surgery and 52 (33, 1%) had a conservative approach. With a median follow-up of 51 months, 2 patients in the surgical group had a local recurrence and 8 in the conservative group had a LR, respectively. Distance metastasis occurred in 7 and 1 patients of surgical and conservative group, respectively. No differences were detected in terms of survival outcomes except for colostomy free survival (p: 0, 01). The conservative group showed better intestinal (p < 0.01) and sexual (p: 0, 04) function and emotional status (p: 0, 02). Conclusions: Conservative approach seems to be safe in terms of survival outcomes with a significant advantage on quality of life in RC patients who achieved clinical complete response after nCRT.